Environmental performance of the urban microclimate in pedestrian zones of Tarija, Bolivia - Martínez Mansilla, Maria Eugenia (2021)
One of the main challenges facing the city is the need to improve the conditions of urban mobility and accessibility as fundamental aspects of urban life with social, spatial, functional, and cultural repercussions for adaptation to climate change. For this purpose, analysing thermal comfort and the influence of microclimate as the main factors of determining urban heat islands (UHI) caused by solar radiation from construction materials and surfaces leads to the following research question: How do pedestrian zones affect the microclimate and how can they contribute to thermal comfort? The objective of this article is to evaluate the environmental performance of the urban microclimate in a single street in the historic centre of the city of Tarija. The method consists of applying a simulation with the ENVI-met 4.4.5 software to two scenarios: 1) asphalt road and parking areas, and 2) pedestrian path with vegetation and natural surface materials. The simulated maps present variables of air temperature, T surface, and radiant temperature to determine the level of thermal comfort calculated with the predicted mean vote index (V). The results showed a 6 °C difference in the surface temperature between both scenarios, and the PMV index was comfortable at 9:00, while later, at 12h and 15h, the index improved with the incorporation of vegetation and natural materials on the road surface. Similarly, through remote sensing, 5.14 °C was obtained as the land surface temperature (LST). These indicators spotlight the effects of the change in the urban microclimate to improved decision-making in urban design and argue for a network of pedestrian areas in the city.